2021
DOI: 10.1126/scitranslmed.abe8146
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals SARS-CoV-2 infection dynamics in lungs of African green monkeys

Abstract: Detailed knowledge about the dynamics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is important for uncovering the viral and host factors that contribute to coronavirus disease 2019 (COVID-19) pathogenesis. Old-World nonhuman primates recapitulate mild to moderate cases of COVID-19, thereby serving as important pathogenesis models. We compared African green monkeys inoculated with infectious SARS-CoV-2 or irradiated, inactivated virus to study the dynamics of virus replication thro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
172
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(191 citation statements)
references
References 53 publications
(79 reference statements)
17
172
2
Order By: Relevance
“…Samples (swabs/organs) that tested positive for viral genomic RNA were evaluated using assays specifically detecting sgRNA. The assay detecting sgRNA of the E-gene established by Speranza et al 32 with the modification of omitting the ZEN™ quencher was used. In addition, a further assay was applied to detect sgRNA of the ORF7a, as Alexandersen and colleagues 33 demonstrated that this sgRNA is more abundantly quantifiable.…”
Section: Methodsmentioning
confidence: 99%
“…Samples (swabs/organs) that tested positive for viral genomic RNA were evaluated using assays specifically detecting sgRNA. The assay detecting sgRNA of the E-gene established by Speranza et al 32 with the modification of omitting the ZEN™ quencher was used. In addition, a further assay was applied to detect sgRNA of the ORF7a, as Alexandersen and colleagues 33 demonstrated that this sgRNA is more abundantly quantifiable.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to other common respiratory viruses, SARS-CoV-2 appears to elicit poor type I interferon responses in cultured human epithelial cells, and instead skews towards proinflammatory cytokine profiles, in line with observations from human peripheral studies 21,37,38 . To directly assay virally-targeted cell types or tissues in vivo, researchers have relied on emerging animal models, including non-human primates 4547 , hamsters 48,49 , mice 5053 , and ferrets 54,55 . These animal models vary widely in the severity of SARS-CoV-2-driven disease and associated immunopathology, and incompletely reflect the diversity of viral infection outcomes and natural immune responses within the human population 56 .…”
Section: Introductionmentioning
confidence: 99%
“…Public health agencies leverage sequencing technology to provide critical data for viral surveillance of SARS-CoV-2 variants. Moreover, single-cell RNA sequencing can also firmly address COVID-19 infection along with the strong guidance of previous literature study [ 66 ].…”
Section: Advent Towards Detection Methodsmentioning
confidence: 95%